2020
DOI: 10.1177/0301006620905216
|View full text |Cite
|
Sign up to set email alerts
|

Turning Heads: The Effects of Face View and Eye Gaze Direction on the Perceived Attractiveness of Expressive Faces

Abstract: We investigated whether the perceived attractiveness of expressive faces was influenced by head turn and eye gaze towards or away from the observer. In all experiments, happy faces were consistently rated as more attractive than angry faces. A head turn towards the observer, whereby a full-face view was shown, was associated with relatively higher attractiveness ratings when gaze direction was aligned with face view (Experiment 1). However, preference for full-face views of happy faces was not affected by gaze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…Notably, happy facial expressions have consistently been associated with a multitude of positive social attributions, encompassing qualities such as sincerity, competence, sociability (Reis et al, 1990 ), trustworthiness (Calvo et al, 2018 ), familiarity, and overall positivity (Garrido et al, 2017 ). This influence extends to attractiveness perception, where studies have consistently shown that individuals tend to rate happy facial expressions as more attractive than neutral or angry expressions (Calvo et al, 2018 ; Garrido et al, 2017 ; Ho & Newell, 2020 ; Kaisler et al, 2020 ; Lindeberg et al, 2019 ; Reis et al, 1990 ; Ueda et al, 2016 ). Moreover, these investigations suggest that attractiveness perception is intricately linked to emotional expression, with the valence (positive or negative) and intensity of the emotion further shaping these judgments (Ueda et al, 2016 ).…”
Section: Available Face and Voice Databasesmentioning
confidence: 96%
“…Notably, happy facial expressions have consistently been associated with a multitude of positive social attributions, encompassing qualities such as sincerity, competence, sociability (Reis et al, 1990 ), trustworthiness (Calvo et al, 2018 ), familiarity, and overall positivity (Garrido et al, 2017 ). This influence extends to attractiveness perception, where studies have consistently shown that individuals tend to rate happy facial expressions as more attractive than neutral or angry expressions (Calvo et al, 2018 ; Garrido et al, 2017 ; Ho & Newell, 2020 ; Kaisler et al, 2020 ; Lindeberg et al, 2019 ; Reis et al, 1990 ; Ueda et al, 2016 ). Moreover, these investigations suggest that attractiveness perception is intricately linked to emotional expression, with the valence (positive or negative) and intensity of the emotion further shaping these judgments (Ueda et al, 2016 ).…”
Section: Available Face and Voice Databasesmentioning
confidence: 96%
“…Some studies have investigated the aesthetic perception of faces using CFD in non-US populations. For example, in populations from Germany (Klümper et al, 2020;Mertens et al, 2021), Italy (Balconi et al, 2020), Ireland (Ho and Newell, 2020), Australia (Ecker and Rodricks, 2020;White et al, 2021), and specifically in studies investigating the aesthetics perception of faces and its relationship with facial asymmetry, such as in a population from the Netherlands (Roth et al, 2022), England (Aksentijevic et al, 2021, Brazil (Monteiro et al, 2022), or those that do not report where the participants are from Lee et al (2021) and Staller and Randler (2021).…”
Section: Introductionmentioning
confidence: 99%